Umbelliferone Inhibits Spermatogenic Defects and Testicular Injury in Lead-Intoxicated Rats by Suppressing Oxidative Stress and Inflammation, and Improving Nrf2/HO-1 Signaling [Retraction] - Alotaibi MF; Al-Joufi F; Abou Seif HS; Alzoghaibi MA; Djouhri L; Ahmeda AF; Mahmoud AM (Dove Medical Press, 2023)
Alotaibi MF, Al-Joufi F, Abou Seif HS, et al. Drug Des Devel Ther. 2020;14:4003-4019 The Editor and Publisher of Drug Design, Development and Therapy are retracting the published article. Concerns were raised regarding the duplication of images in Figure 2 and an investigation found overlap in the images for Figures 2D and 2E, despite both images representing results of different treatments. The authors cooperated with the investigation and provided data associated with the reported study. However, despite the authors’ assistance, a satisfactory explanation for how the images came to be duplicated could not be provided, and the validity of the published work could not be verified. The decision was made to retract the article and the authors were notified of this. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”.